2020
DOI: 10.3390/en13030563
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Investigation of Nanocrystalline Hydrogen-Storing Mg-Titanate Nanotube Composites Processed by High-Pressure Torsion

Abstract: A high-energy ball milling and subsequent high-pressure torsion method was applied to synthesize nanocrystalline magnesium samples catalyzed by TiO2 or titanate nanotubes. The microstructure of the as-milled powders and the torqued bulk disks was characterized by X-ray diffraction. The recorded diffractograms have been evaluated by the convolutional multiple whole profile fitting algorithm, which provided microstructural parameters (average crystal size, crystallite size distribution, average dislocation densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 62 publications
(76 reference statements)
1
13
0
Order By: Relevance
“…It was also shown that HEBM parameters also significantly affect the sorption performance of the final Mg-NbO-CNT HPT samples [95]. In a very recent paper, we have shown that the combined catalytic effect of metaloxide particles and CNTs can be replaced by applying only titanate nanotubes (TN) [96], note that this research is still in progress. In this preliminary work, the HEBM+HPT deformation route was applied on nanocrystalline Mg powders catalyzed by TN.…”
Section: Nanocrystalline Mg Catalyzed By Nanotube Additivesmentioning
confidence: 96%
See 1 more Smart Citation
“…It was also shown that HEBM parameters also significantly affect the sorption performance of the final Mg-NbO-CNT HPT samples [95]. In a very recent paper, we have shown that the combined catalytic effect of metaloxide particles and CNTs can be replaced by applying only titanate nanotubes (TN) [96], note that this research is still in progress. In this preliminary work, the HEBM+HPT deformation route was applied on nanocrystalline Mg powders catalyzed by TN.…”
Section: Nanocrystalline Mg Catalyzed By Nanotube Additivesmentioning
confidence: 96%
“…As was shown the HPT processing results in the decrease of the average crystallite size of HEBM Mg powders and at the same time a strong texture was also developed. In addition, the processing route considerably influences the H-sorption kinetics, i.e., the hydrogenation performance (capacity and kinetics) of the composite produced for longer co-milling of TN together with Mg significantly exceeds the sorption properties of the specimen when In a very recent paper, we have shown that the combined catalytic effect of metal-oxide particles and CNTs can be replaced by applying only titanate nanotubes (TN) [96], note that this research is still in progress. In this preliminary work, the HEBM+HPT deformation route was applied on nanocrystalline Mg powders catalyzed by TN.…”
Section: Nanocrystalline Mg Catalyzed By Nanotube Additivesmentioning
confidence: 99%
“…Recently, titanate nanotubes prepared using the hydrothermal method from anatase TiO 2 was applied to improve the sorption properties of magnesium using high-energy ball milling and high-pressure torsion. The morphological differences due to the variation of the milling time were found to have a significant impact on the absorption kinetics of Mg [149]. Another group synthesized Na 2 Ti 3 O 7 nanotubes and nanorods using the hydrothermal and solid-state method, respectively (see Figure 14), and mixed them to MgH 2 in a planetary ball mill.…”
Section: Catalysts With Special Morphologymentioning
confidence: 99%
“…The hydrogenation performance of different non-equilibrium alloys can be significantly improved when the material is subjected to a massive severe plastic deformation technique called high-pressure torsion (HPT) [40][41][42][43][44][45][46]. Among the different deformation methods, HPT exhibits the largest equivalent strain [47].…”
Section: Introductionmentioning
confidence: 99%